Phyto Analysis, Formulation, and Evaluation of Herbal Lotion Produced From Allium Sativum and Phyllanthus Emblica Alcoholic Extracts - Raj, Mukut; Vyas, Girish Kumar; Sharma, Shailesh; Sharma, Anil (Asian Journal of Pharmaceutical Research and Development, 2022)
Herbal cosmetics are concoctions that are used to beautify and improve the look of humans. The purpose of this study was to develop and test a herbal antibacterial lotion formulation that included an alcohol-based fruit extract. Recent research in numerous parts of the world has found that the active components of Allium sativum and Phyllanthus emblica fruits have a great potential for treating a wide range of health conditions. Microbial/worm infection can be efficiently combated using Allium sativum and Phyllanthus emblica preparations. It's anti-inflammatory, anti-cancer, and anti-microbial. The prepared lotion displayed good consistency and spreadability, homogeneity, pH, non-greasy, and no symptoms of phase separation during the research period. Stability properties of the produced lotion, such as visual appearance, nature, viscosity, and scent, did not change significantly during the study time.